Effects of interactive metronome on the changes in arm angle and motor timing in the upper extremity during a golf putt - Kim, J. H.; Ridgel, A. L.; Han, D. H. (International Journal of Performance Analysis in Sport, 2020)
The goal of this study was to examine if motor timing training alters the variability of the upper extremity movement during the golf putt. To improve motor timing, we utilised Interactive Metronome (IM), a software program that is designed to improve the rhythm and timing of intrinsic movements. Twenty participants who were registered in the Korea Ladies Professional Golf Association were randomly assigned to either an IM or control group. The IM group completed 12 motor timing sessions and the control group practised the golf putt swing alone over 12 sessions. Outcome measures, which were measured pre- and post-test, included: 1) arm angle during three parts of the swing section: Arm angle during the setup, impact and finish of the swing and motor timing was measured before and after the intervention. 2) motor timing measures of the right, left and both arms together. Variability of the arm angle was reduced during the putt (F (1,18) = 5.956, p = 0.025) setup. Motor timing of the right (F (1,18) = 4.922, p =.040) and left (F (1,18) = 4.904, p =.040) arms improved. This study shows that IM training can improve motor timing in the upper extremity and reduce variability in the arm motion during the golf putt.